ESTUDO DO ZINCO PLASMATICO E HEMATICO NA DESNUTRICAO PROTEICO CALORICA EXPERIMENTAL - Denardi, F.; Ancona Lopez, F.; Dias Bastos, H.; De Nobrega, F. J. (My University, 1977)
Plasma and red cell zinc was assayed by atomic absorption spectrophotometry in three groups of male rats, 58 days old, weaned in the 30th day of life. Control group (20 rats) was fed with normal lab diet while the kwashiorkor group (20 rats) received a protein-free diet and the marasmic group (15 rats) received a protein calorie deficient diet. The clinical and biochemical data obtained in the different groups agreed with the nutritional state. A lower and similar concentration of Zinc in plasma and red cells was observed among both malnourished groups. In this paper the authors discuss the results and present a review of the literature concerning the role of zinc in nutrition.
Zinc content of plasma and erythrocytes in experimental protein calorie malnutrition (rat)
Keywords: diagnosis; erythrocyte zinc; in vitro study; marasmus; methodology; model; rat; theoretical study; zinc blood level